A tortuous proximal urethra in urorectal septum malformation sequence?. Issue 5 (24th March 2014) - Lin, Henry J.; Lugo, Hector; Tran, Thu; Tovar, Jason P.; Corral, Julia; Zork, Noelia M.; Smith, Lynne M.; French, Samuel W.; Barajas, Luciano
<x xml:space="preserve">Abstract</x> We observed a newborn boy with urorectal septum malformation sequence. Anomalies of the genitalia and rectum were present. He expired on the first day of life, due to severe lung hypoplasia. Autopsy showed a colon that ended in a blind sac, an enlarged bladder with no grossly visible urethra, and dysplastic kidneys. A cone‐shaped tissue at the usual site of the bladder outlet contained tortuous and slit‐like lumina, suggesting an undeveloped proximal urethra. The urethral structure was lined by transitional epithelium with squamous metaplasia. Many small buds—lined with columnar epithelium—branched from the urethral structure. These ductal buds lined with columnar epithelium stained for prostatic acid phosphatase. Basal cells surrounding the ductal buds stained for p63 and high molecular weight cytokeratin—supporting an interpretation that the buds were early prostatic ducts with normal histology. To our knowledge, these are the first histological images of an undeveloped, obstructed urethra associated with the urorectal septum malformation sequence. © 2014 Wiley Periodicals, Inc.